Spanish Employment Legislation Reforms in the Recent Crisis - Towards a New Model of the Industrial Relations System - Ortega, Fernando Fita (Olsztyn Economic Journal, 2014)
The recent crisis and its consequences have induced major changes in Spanish employment legislation which may lead into what could be recognized as a new model of the industrial relations system. Since the early 90’s, and as a reaction to globalization, the need of introducing measures for promoting adaptability and flexibility have had echoes in Spanish employment legislation. However, the crisis we are experiencing nowadays is having a greater impact upon the Spanish economy, and hence on employment regulations, than any other previous crisis. The legislature’s reaction in order to reverse the situation is leading to a new model of the industrial relations system, since this is happening in the whole European Union, where the power of collective bargaining has been undermined, and with it the role of trade unions. This has had a huge impact on the essence of Spanish labour law (derecho del trabajo). These regulations seek to protect employees at their working places from the managerial power of the employer, but without forgetting the need of protecting the efficiency of the enterprise. In fact, after the new legislation following the political decisions of the Spanish Government, we are closer than ever to an Employment Law (derecho alempleo) where the protection is focused on the citizens’ ability to work, protecting them in the labour market. The aim of this paper is to give a short description of the Spanish labour market’s situation showing the most relevant data; to provide an analysis of the main measures introduced into Spanish employment legislation, and to draw some conclusions about where and why some decisions are made and what consequences they have for the industrial relations system.